0184 Predicting Strategic Napping in Surgical Residents by Individual and Rotation Characteristics. (27th May 2020) - Devine, J K; Schwartz, L P; Hursh, S R; Mosher, E; Schumacher, S; Boyle, L; Davis, J E; Smith, M; Fitzgibbons, S
Abstract: Introduction: Strategic napping, or napping on-shift, is recommended to reduce fatigue in medical residents. The actual prevalence of strategic napping in relation to residents' workload, schedule, or demographics is largely unquantified. This study objectively measured sleep patterns and work schedules in surgical residents working a variety of service lines over a two-month period in order to identify which resident and service line attributes predict on-shift napping. Methods: Surgical residents from an academic surgery program in the Washington, DC area provided schedule information, completed the Epworth Sleepiness Scale (ESS), and wore sleep-tracking devices (Zulu Watch) continuously for 8 weeks. Multiple linear regression was performed to predict percent days with on-shift napping from resident demographics (age, gender, post graduate year (PGY), sleep characteristics (ESS, total sleep time (TST), sleep efficiency (SE)), schedule characteristics (shift start time, shift length, rotation length, percent days on-shift, percent night shifts), and service line characteristics (service line category, number of service lines worked). Results: Twenty-two (n=22) residents completed the study, rotating through at least 1 of 5 different service line categories (Acute Non-Elective Surgery, Elective Surgery, Night Float, Surgical Intensive Care Unit, and Other). Residents slept an average of 6 hours within a 24-hour period (370±129 minutes) with normal SE (87.13%±7.55%). ESS scores indicated excessive daytime sleepiness (11.64±4.03). Ninety-five percent (n=21) of residents napped at least once while on shift. Residents napped on-shift approximately 32% of their working days and were most likely to nap when working between 2300-0500 hours. Earlier shift start times predicted less on-shift napping (B=-0.08, SE=0.04, β=-2.40, t=-2.09, p=0.05) while working more night shifts (B=1.55, SE=0.44, β=4.12, t=3.52, p=0.003) and shifts over 24 hours. Conclusion: Residents take advantage of opportunities to nap on-shift, particularly when working at night. Despite naps, however, residents exhibit insufficient sleep with excessive daytime sleepiness, representing a safety risk to themselves and their patients. Support: NA